Does an empowerment-based self-care supportive intervention save cost for improving self-care and health service utilization among heart failure patients. (14th October 2021) - Yu, D.S.F; Li, P.W.C; Yu, S; Yan, B; Wong, J
Abstract: Background: Heart failure (HF) evolves as a global pandemic and strains the over-stretched hospital service. Ineffective self-care remains the key factor to explain the avoidable hospital admission. Patient empowerment is as a theory-based strategy to optimize the patients' self-care changes for disease management [1]. Its cost-effectiveness to enhance self-care and health service utilization has yet to be determined. Purpose: This was a double-blind randomized controlled trial to compare the effects and cost-effectiveness of a 12-week empowerment self-care program with a didactic education program on self-care maintenance and management as well as health service utilization among the community-dwelling HF patients. Methods: A total of 236 HF patients were recruited from the specialist clinics of the Department of Cardiology in two regional hospitals. They were randomized to receive either the 12-week empowerment self-care program (Figure 1) or the 12-week didactic education. Outcome evaluation using the Self-care Heart Failure Index (SCHFI) at baseline, post-intervention (T1) and three months thereafter (T2), with record on the number of emergency room (ER) attendance and hospital admission. Cost effectiveness analyses were performed on total cost (medical, intervention and societal costs) incurred in both interventions as well as incremental cost-effectiveness ratios (ICER) expressed as incremental cost per 1) a reflected clinically meaningful improvement in self-care (i.e. a half standard deviation increase in SCHFI), 2) an ER attendance reduced, 3) a day of hospital stay reduced. Results: As compared with the education group, the empowerment group reported significantly greater improvement in self-care management at T1 [B=13.77 (95% CI=6.07, 21.46), p<0.001] and T2 [B=10.98 (95% CI=3.21, 18.75), p=0.006]. For cost-effective analysis, The ICER (empowerment-education) was −USD220/0.5 SD increase in SCHFI, indicating the mean cost saved per patient for making a clinically significant improvement in self-care was USD 220. The cost-effectiveness acceptability curve showed patients were willing to pay at USD 207- 441 for a 80–90% chance of improved self-care, indicating that the empowerment approach was a cost saving strategy. Although the empowerment approach was associated with a lower risk of ER attendance [IRR=0.55, 95% CI=0.31–0.95)] and hospital admission [IRR=0.38 (95% CI=0.31–0.95)], it is not cost saving for reducing hospital service utilization. Conclusions: The empowerment-based self-care program is a cost-saving strategy to produce a clinical significant change in HF-related self-care. Although it is associated with lower risk for hospital service utilization, its effect is not significant enough to be cost-saving. Future care model may explore the need to integrate dyadic science [2] and e-health [3] to strengthen the care continuity and effects of self-care intervention. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Health and Medical Research Fund, Food and Health Bureau, Hong Kong Special Administrative Region